Analysis of Combustion Characteristics and Emissions of Diesel Engine Fueled With Waste Source Fuel - Abdul Adam, Abdullah; Nur Atiqah, Ramlan; Nur Fauziah, Jaharudin; Mohd Herzwan, Hamzah; Mohd Fahmi, Othman (2016)
Since the 18th century Industrial Revolution, fossil fuel has been the main energy source used to power the economy and becoming the global energy prominence until today. Furthermore, the advance in drilling technology in mid-19th century lead to the petroleum as a highly resourceful energy source powering transportation such as automobiles, ships, and even to generate electricity. The recent oil depletion crisis force many researchers to conduct a search to the new source of energy. In conjunction, the modernization also sees the new global problem such as an increment of waste products such as tires, plastic and cooking oil around the globe. Utilization of these waste products as an alternative fuel can reduce the dependent to the fossil fuel. In this paper, alternative fuels derived from the waste sourced fuels are discussed. Three type of waste sourced fuels are tire disposal fuel (TDF), waste plastic disposal fuel (WPD) and waste cooking oil (WCO). The combustion characteristics of the waste fuels are compared to diesel fuel (DF). The combustion curve and exhaust emissions of these pure concentrated fuels are discussed in this paper. The results indicate that WCO show comparable combustion characteristics and exhaust emission to DF. TDF can run at low engine speed but not at high engine speed due to the backfire phenomenon occurs when engine running at high speed region.